MENINGKATKAN AKHLAK ANAK MELALUI KEGIATAN MENGHAFAL DO'A HARIAN DALAM DIDIKAN SUBUH DI MASJID JAMI' DESA BANTAN AIR - Nur'aina, Nur'aina; Nisa, Khairun (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
This study aims to improve children's morals through memorization activities of daily prayers in dawn education at Jami' Mosque, Bantan Air Village. Memorizing daily prayers can shape children's morals and improve their relationship with God. Religious practices also help in the development of children's character and spiritual awareness. Introducing children to religious practices is important to shape their moral values. Remembering daily prayers helps children in strengthening their relationship with God and developing spiritual awareness. Memorizing daily prayers in Islam can help children internalize religious values and teachings. The prayers contain moral, ethical, and instructional messages about living a righteous life. By memorizing daily prayers, children can develop a stronger sense of religious identity and feel more connected to their religion. Daily prayers also teach values such as patience, compassion, honesty, humility, and justice. Memorizing daily prayers requires consistency and discipline, which can help children in establishing positive tendencies and discipline in their routines. In addition, daily prayers also help children in facing difficulties and trials in their lives, as they learn how to ask God for help and wisdom. Overall, memorizing daily prayers has many benefits in improving the morals and ethics of Islamic children